Processes and Activities for Managing Change in Information Systems Implementation in Higher Education Institution - Manzilatul Rohmah; Apol Pribadi Subriadi (The Winners, 2022)
The research aimed to develop a model for managing change consisting of detailed processes and activities that include changes in technology, organizations, and individuals in the implementation of information systems. The change management model developed in the research was used as a guideline for managing changes that occur when implementing changes in information systems in higher education. This change management model was developed using the action research method to obtain a model that fits the practical conditions. The model included the process and details of activities which were obtained in two ways, namely by identifying the success factors of implementing information systems in previous studies and interviewing information system implementers in tertiary institutions to obtain practical change management activities. The proposed change management model has been verified and validated where the results show that the process in the model is in accordance with expert theory. The results of using this model indicate that the management of changes in information systems can be carried out in a clearer and more structured.